Is innovative firm behavior correlated with age and gender composition of the workforce? Evidence from a new type of data for German enterprises - Christian Pfeifer; Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2012)
This empirical research note documents the relationship between composition of a firm's workforce (with a special focus on age and gender) and its performance with respect to innovative activities (outlays and employment in research and development (R&D)) for a large representative sample of enterprises from manufacturing industries in Germany using unique newly available data. We find that firms with a higher share of older workers have significantly lower proportions of R&D outlays in total revenues and of R&D employment in total employment, whereas firms with a higher share of female employment seem to be more active in R&D.
Keywords: D22; D24; J21; J24; L25; 330; Ageing; firm performance; gender; Germany; innovation; R&D; Innovation; Industrielle Forschung; Ältere Arbeitskräfte; Weibliche Arbeitskräfte; Verarbeitendes Gewerbe; Altersgruppe; Geschlecht; Deutschland